Presupposition Triggers of Teacher Talk in Higher Education - Tyas, Umi Aisyah Sulistyaning; Rukmini, Dwi; Wuli Fitriati, Sri (English Education Journal, 2020)
The present study is aimed at investigating the way of presupposition triggers realized in the lecturer talk. This qualitative research is conducted in English class of the State Institute for Islamic Studies (IAIN) Salatiga by purposive sampling. The present study serves reading class recordings as the data. Reading class was chosen for the reason of similar process in making prediction on reading, i.e. schemata theory, with presumption on presupposition. It is equipped by observation and documentation in order to enhance confidence in the ensuing findings. The finding shows that presupposition triggers realized by the several categories; they are definite description, factive verb, implicative verb, change of state verb, iterative, verb of judging, temporal clause, comparison and contrast, non-restrictive relative clause, and question. The most frequent used category is definite description, with the simple structure of possessive construction and definite noun phrase. Another important result is the preference to use question as the next favored triggers.